A negative electrode current collector, a method of manufacturing a negative electrode current collector, and a battery
Patent Information
- Application Number
- CN202611336137.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]为了解决复合集流体的耐高温性能较差、层间结合力较差和焊接良率不足的问题,本发明提供了一种负极集流体、制备该负极集流体的方法和包括该负极集流体的电池
在本发明的负极集流体中,基材层由功能层和主体层构成,在基材层的厚度方向上,功能层位于主体层的两侧表面,铜箔层位于两侧的功能层远离所述主体层一侧的表面;功能层的成分包括若干个交联结构,所述交联结构包括链状结构单元和交联结构单元,所述交联结构单元以共价键的形式连接至少两个所述链状结构单元。
Smart Images

Figure CN122992086A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically to a negative electrode current collector, a method for preparing the negative electrode current collector, and a battery including the negative electrode current collector. Background Technology
[0002] Lithium-ion batteries are widely used in new energy vehicles, energy storage, and 3C digital products due to their superior performance, including high energy density, high operating voltage, and long cycle life. With societal development and increased competition among companies, higher demands are being placed on the energy density of lithium batteries. Therefore, improving the mass energy density of lithium-ion batteries is a pressing technical challenge that needs to be addressed. Summary of the Invention
[0003] In traditional lithium-ion batteries, copper foil is used as the negative electrode current collector. Since copper foil accounts for a significant portion of the battery's mass, reducing its weight is an effective way to improve the energy density of lithium-ion batteries. Currently, composite current collectors are being used. These are composite current collectors that use a polymer substrate and deposit a copper foil layer of a certain thickness onto the thin film using physical, chemical, and electrochemical methods. This composite current collector not only improves the energy density of lithium-ion batteries but also enhances their safety performance. However, research has revealed two problems with the welding of composite current collectors based on polyethylene (PE) and / or polypropylene (PP): First, the base film has poor high-temperature resistance and is prone to melting and softening. The principle of commonly used ultrasonic welding is to generate heat through high-frequency vibration and friction, causing local melting of the metal to achieve connection. Although the welding time is extremely short (milliseconds), the heat generated can still be quickly conducted through the thin copper layer to the underlying polymer base film. The glass transition temperature and melting point of polymer materials are much lower than those of metals, so the base film will quickly soften, melt, or even decompose during welding. Second, the composite current collector has poor structural stability and is prone to interlayer delamination. The "sandwich" structure (copper foil-polymer base film-copper foil) of the composite current collector relies on the adhesion between the polymer base film and the metal coating. Once the base film melts, this adhesion will be severely damaged or even completely lost, causing the copper layer and the base material in the welding point and surrounding area to delaminate or blister, resulting in insufficient welding yield and affecting the safety performance of the battery.
[0004] To address the issues of poor high-temperature resistance, weak interlayer bonding, and insufficient welding yield in composite current collectors, this invention provides a negative electrode current collector, a method for preparing the negative electrode current collector, and a battery including the negative electrode current collector. The negative electrode current collector of this invention exhibits high high-temperature resistance and high structural stability. During the welding process, it can reduce or even avoid melting and softening, as well as interlayer delamination, thereby improving the high-temperature resistance and structural stability of the negative electrode sheet, increasing welding yield, and ultimately enhancing battery safety performance.
[0005] To achieve the above objectives, the first aspect of the present invention provides a negative electrode current collector, the negative electrode current collector comprising a substrate layer and a copper foil layer, the substrate layer comprising a functional layer and a main body layer, wherein in the thickness direction of the substrate layer, the functional layer is located on both sides of the main body layer, and the copper foil layer is located on the side of the functional layer away from the main body layer. The functional layer comprises several cross-linked structures, each including chain structural units and cross-linked structural units. Each cross-linked structural unit connects at least two chain structural units in the form of covalent bonds. Based on the total weight of the substrate layer, the weight percentage of the cross-linked structures is 5%-50%.
[0006] A second aspect of the present invention provides a method for preparing the negative electrode current collector described in the first aspect of the present invention, the method comprising the following steps: S1: Pretreatment: The base film is subjected to atmospheric pressure plasma treatment to obtain a hydrophilic base film; S2: Modification preparation of a substrate layer with a functional layer on the surface: A photoinitiator, a crosslinking monomer, and a first solvent are brought into a first contact to form a first solution. The first solution is coated onto the surface of the hydrophilic base film through a first coating process to form a substrate layer including a wet film. The substrate layer including the wet film is placed in an oven for a first treatment, and then the temperature of the oven is adjusted for a second treatment to obtain a substrate layer including a dry film. The substrate layer including the dry film is placed under an ultraviolet light source for irradiation, so that the surface of the substrate layer undergoes a crosslinking reaction to obtain a substrate layer including a functional layer. S3: Prepare a metal layer on the surface of the functional layer: deposit a first copper foil layer on the opposite two sides of the substrate layer including the functional layer, and form a second copper foil layer by electroplating on the surface of the first copper foil layer.
[0007] A third aspect of the present invention provides a battery comprising a negative electrode sheet, the negative electrode sheet comprising the negative electrode current collector described in the first aspect of the present invention and / or the negative electrode current collector prepared by the method described in the second aspect of the present invention.
[0008] By employing the above technical solution, the present invention has at least the following advantages compared with the prior art: In the negative electrode current collector of the present invention, the substrate layer is composed of a functional layer and a main layer. In the thickness direction of the substrate layer, the functional layer is located on both sides of the main layer, and the copper foil layer is located on the side of the functional layer away from the main layer. The functional layer is composed of several cross-linked structures, and the cross-linked structure includes chain structural units and cross-linked structural units. The cross-linked structural units are connected by at least two chain structural units in the form of covalent bonds.
[0009] Research has revealed that the poor high-temperature resistance of polymer basement membranes is due to their chain-like structure. These chains are physically entangled and subject to weak van der Waals forces. This physical entanglement and weak van der Waals forces are transient, resulting in slippery physical contact points with poor stability. Macroscopically, this manifests as a lower melting temperature and fluidity in the molten state, thus leading to poor high-temperature resistance. In the negative electrode current collector of the present invention, the functional layer comprises several cross-linked structures. The cross-linked structures include chain structural units and cross-linked structural units. The cross-linked structural units connect at least two chain structural units in the form of covalent bonds. That is, one cross-linked structural unit can connect at least two chain structural units together to form a chemical cross-linking point. Several cross-linked structural units can connect several chain structural units together to form several chemical cross-linking points, thereby forming a stable three-dimensional network structure in the functional layer. This three-dimensional network structure can restrict the flow of chain structural units, increase the melting temperature and high temperature resistance of the substrate layer, reduce or even avoid the risk of melting and softening of the substrate layer, and improve the welding yield. However, if there are too many cross-linked structures in the functional layer, the chain structure becomes over-crosslinked, and the three-dimensional network structure is prone to problems such as embrittlement and stress concentration, which leads to a decrease in the high-temperature resistance of the functional layer. Based on this, the cross-linked structure in the negative electrode current collector control substrate layer of the present invention accounts for 5%-50% of the weight. This can not only build a more stable three-dimensional network structure in the functional layer, restrict the flow of chain structure units, and improve the melting temperature and high-temperature resistance of the substrate layer, but also avoid the problems caused by excessive cross-linking of chain structure units in the functional layer, which can affect the high-temperature resistance of the negative electrode current collector.
[0010] Other features and advantages of the present invention will be described in detail in the following detailed description section.
[0011] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. Attached Figure Description
[0012] Figure 1 The figure shown is a schematic diagram of the cross-sectional structure of the negative electrode current collector of the present invention. Detailed Implementation
[0013] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the invention. Unless otherwise specified herein, data ranges include endpoints.
[0014] It should be noted that the numerical designations such as "first" and "second" in this invention are only used to distinguish different substances or methods of use, and do not represent a difference in order.
[0015] The first aspect of this invention provides a negative electrode current collector, such as... Figure 1 As shown, the negative electrode current collector 1 includes a substrate layer 11 and a copper foil layer 12. The substrate layer 11 is composed of a functional layer 111 and a main layer 112. In the thickness direction X of the substrate layer 11, the functional layer 111 is located on both sides of the main layer 112, and the copper foil layer 12 is located on the side of the functional layer 111 away from the main layer 112.
[0016] It is understood that in the structure of the negative electrode current collector of the present invention, the substrate layer includes a functional layer, which is part of the substrate layer and is located on the surface of the substrate; the copper foil layer is located on the surface of the functional layer, or it can be considered that the copper foil layer is located on the surface of the substrate layer.
[0017] The functional layer may include several cross-linked structures, each cross-linked structure comprising chain structural units and cross-linked structural units. Each cross-linked structural unit is covalently linked to at least two (e.g., 2 or 3) chain structural units. Based on the total weight of the substrate layer, the weight percentage of the cross-linked structures is 5%-50% (e.g., 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50%). The functional layer may also include polar groups selected from at least one of ester groups, isocyanurate cyclic groups, hydroxyl groups, ether groups (ether bonds), and carbonyl groups.
[0018] In this invention, a chain-like structural unit refers to a structure with a long, linear chain-like framework, where atoms in the framework are covalently linked end-to-end to form a one-dimensional, continuously extending chain. It is understood that the chain-like structural unit may or may not include branches. Branches refer to atoms or atomic groups that are covalently linked from the framework atoms and do not participate in the construction of the one-dimensional continuous framework.
[0019] In this invention, "the cross-linked structural unit is connected to at least two chain structural units in the form of covalent bonds" means that the cross-linked structural unit is connected to atoms in the skeleton of at least two different chain structural units in the form of covalent bonds.
[0020] In this invention, the weight percentage of the crosslinked structural units, based on the total weight of the substrate layer, can be obtained by the following method: Take approximately 0.3-0.5g of the sample along the width or length of the substrate layer (it is understood that the structure of the substrate layer in the thickness direction should not be damaged during the acquisition of the sample), wrap it in a stainless steel mesh bag with a known constant weight M0, dry it at 80°C, and weigh it to obtain the total weight M1 before extraction; place the mesh bag in a Soxhlet extractor, and continuously extract it for 12-24 hours using boiling xylene containing 0.5% antioxidant (2,6-di-tert-butyl-4-methylphenol) as the extractant, until the reflux condensate becomes colorless. Remove the mesh bag, rinse it with fresh xylene, then wash it with acetone, and then dry it in a vacuum oven at 80°C to a constant weight to obtain the total weight M2 after extraction; based on the total weight of the substrate layer, the weight percentage (%) of the crosslinked structural units = [(M2-M0) / (M1-M0)] × 100%. The principle of the above test method is that the cross-linked structure only swells and does not dissolve in boiling xylene.
[0021] In this invention, by setting a functional layer on the surface of the substrate layer and simultaneously controlling the composition of the functional layer and the weight ratio of cross-linked structural units in the substrate layer, compared with the prior art, it is possible to enable the substrate layer of the negative electrode current collector to have higher high-temperature resistance and the negative electrode current collector to have higher structural stability, thereby improving the welding yield of the negative electrode current collector and thus enhancing the safety performance of the battery. To further improve the effect, one or more of the technical features can be further optimized.
[0022] To improve the adhesion between the substrate layer and the copper foil layer, this invention introduces polar groups into the composition of the functional coating. These polar groups are selected from at least one of ester groups, isocyanurate cyclic groups, hydroxyl groups, ether groups, and carbonyl groups. These polar groups have strong polarity and can coordinate and adsorb with copper oxide and / or cuprous oxide on the surface of the copper foil layer. This enhances the intermolecular forces at the interface between the functional layer and the copper foil, thereby improving the adhesion between them, reducing or even preventing interlayer delamination between the substrate layer and the copper foil layer, improving the structural stability of the negative electrode current collector, increasing the welding yield of the negative electrode current collector, and ultimately improving the safety performance of the battery.
[0023] In some embodiments, the repeating units of the chain-like structural unit are selected from... -[C(R1R2)-C(R3R4)]- , -[O-CH2-CH2-O-CO-C6H4-CO]- One or more of them.
[0024] Among them, R1, R2, R3, and R4 can be the same or different, and each can be independently selected from hydrogen atoms, methyl, ethyl, and propyl groups. Indicates the connection site.
[0025] In some embodiments, the crosslinked structural unit includes at least two (e.g., two or three) connection sites, which are connected to carbon atoms in the backbone of the chain-like structural unit. By connecting the crosslinked structural unit to carbon atoms in the backbone of the chain-like structure, different chain-like structural units can be linked together to form chemical crosslinking points, thereby forming a stable three-dimensional network structure in the functional coating.
[0026] In some embodiments, the crosslinked structural units are selected from... , , -CH2-CH-COO-CH2-CH(CH3)-O-CH2-CH(CH3)-O-CH2-CH(CH3)-O-CO-CH-CH2- , -CH2-CH-COO-(CH2)6-O-CO-CH-CH2- , At least one of them, Indicates the connection site.
[0027] In some embodiments, in the thickness direction of the substrate layer, from the surface of the functional layer to the direction closer to the main layer, the weight percentage of the cross-linked structure in the functional layer decreases. This decreasing weight percentage of the cross-linked structure in the functional layer can improve the high-temperature resistance of the functional layer while retaining the mechanical strength of the base film, thus giving the substrate layer both high high-temperature resistance and high mechanical strength.
[0028] In some embodiments, the crosslinking structural unit is derived from a crosslinking monomer.
[0029] In some embodiments, the crosslinked structural unit includes the polar group.
[0030] In some embodiments, the crosslinking monomer includes one or more of trimethylolpropane triacrylate (TMPTA), triallyl isocyanurate (TAIC), tripropylene glycol diacrylate (TPGDA), 1,6-hexanediol diacrylate (HDDA), and pentaerythritol triacrylate (PETA).
[0031] In some embodiments, the functional layer further comprises structural units derived from a photoinitiator, which are grafted onto atoms in the framework of the chain structural units.
[0032] In some embodiments, the structural unit derived from the photoinitiator is derived from the photoinitiator.
[0033] In some embodiments, the photoinitiator includes one or more of 2-isopropylthioxanthone (ITX), benzophenone (BP), benzoyl dimethyl ketal (BDK), 1-hydroxycyclohexylphenyl ketone, and 2,4,6-trimethylbenzoyl diphenylphosphine oxide (TPO).
[0034] In some embodiments, the residual amount of surface crosslinking monomers and / or photoinitiators in the substrate layer is less than or equal to 2000 ppm (e.g., 2000 ppm, 1800 ppm, 1600 ppm, 1400 ppm, 1200 ppm, 1000 ppm, 800 ppm, 600 ppm, 400 ppm, 200 ppm, 100 ppm, 80 ppm, 60 ppm, 40 ppm, 20 ppm, 10 ppm, 8 ppm, 6 ppm, 4 ppm, 2 ppm, 1 ppm, 0 ppm).
[0035] The residual crosslinking monomers and / or photoinitiators on the surface of the substrate layer exist in molecular form. Since the crosslinking monomers and photoinitiators are small-molecule oily substances, when the residual amount of crosslinking monomers and / or photoinitiators on the surface of the substrate layer is too large, on the one hand, it will contaminate the interface between the substrate layer and the copper foil layer, resulting in low adhesion of the copper foil layer on the surface of the substrate layer, which is not conducive to further improving the structural stability of the negative electrode current collector and further improving the welding yield. On the other hand, at high temperatures (for example, when copper foil is plated by magnetron sputtering, the environment of the magnetron sputtering chamber is a high temperature and high vacuum environment), the small molecules of crosslinking monomers and photoinitiators are easily volatilized or decomposed and release gases when heated. The released gases will disrupt the vacuum environment, the decomposition products will also contaminate the target material, and the released gases will also leave microscopic pinholes in the copper foil layer, affecting the barrier properties of the copper foil layer and the conductivity of the negative electrode current collector. Therefore, from the perspective of further improving the interlayer bonding force of the negative electrode current collector, improving the structural stability of the negative electrode current collector, and improving the high temperature resistance of the substrate layer, the negative electrode current collector of the present invention controls the residual amount of surface crosslinking monomers and / or photoinitiators of the substrate layer within the above-mentioned range.
[0036] It is understood that when only crosslinking monomers remain on the surface of the substrate layer and no photoinitiator is present, the residual amount of crosslinking monomers and / or photoinitiator on the surface of the substrate layer refers to the residual amount of crosslinking monomers on the surface of the substrate layer; when only photoinitiator remains on the surface of the substrate layer and no crosslinking monomers are present, the residual amount of crosslinking monomers and / or photoinitiator on the surface of the substrate layer refers to the residual amount of crosslinking monomers on the surface of the substrate layer; when both photoinitiator and crosslinking monomers remain on the surface of the substrate layer, the residual amount of crosslinking monomers and / or photoinitiator on the surface of the substrate layer refers to the sum of the residual amount of crosslinking monomers and the residual amount of photoinitiator on the surface of the substrate layer.
[0037] In this invention, the residual amount of surface crosslinking monomers and / or photoinitiators in the substrate layer can be obtained by testing methods such as gas chromatography (GC), ultraviolet spectroscopy, etc.
[0038] In some embodiments, the functional layer comprises at least one of unmodified polyethylene, modified polyethylene, unmodified polypropylene, modified polypropylene, unmodified polyethylene terephthalate, and modified polyethylene terephthalate. It is understood that modified polyethylene refers to a polymer formed by crosslinking chain-like polyethylene structures with crosslinking structural units. Modified polypropylene refers to a polymer formed by crosslinking chain-like polypropylene structures with crosslinking structural units. Modified polyethylene terephthalate refers to a polymer formed by crosslinking chain-like polyethylene terephthalate structures with crosslinking structural units.
[0039] In some embodiments, such as Figure 1 As shown, the substrate layer 11 is composed of the functional layer 111 and the main layer 112, and the average pore size of the functional layer is smaller than that of the main layer. Controlling the average pore size of the functional layer to be smaller than that of the main layer can improve the density of the functional layer, further enhance its high-temperature resistance, and also provide more anchor points for polar groups on the surface of the functional layer, thereby further improving the bonding strength between the substrate layer and the copper foil layer, and further enhancing the structural stability of the negative electrode current collector.
[0040] From the perspective of facilitating the embedding of the copper foil layer into the holes of the functional layer and further improving the interlayer bonding force of the negative electrode current collector, the negative electrode current collector of the present invention controls the ratio of the average pore size of the main body layer to the average pore size of the functional layer to be 1.1-1.3 (e.g., 1.1, 1.12, 1.14, 1.16, 1.18, 1.2, 1.22, 1.24, 1.26, 1.28, 1.3).
[0041] In some embodiments, the average pore size of the host layer is 30nm-50nm (e.g., 30nm, 32nm, 34nm, 36nm, 38nm, 40nm, 42nm, 44nm, 46nm, 48nm or 50nm).
[0042] In some embodiments, the average pore size of the functional layer is 25nm-40nm (e.g., 25nm, 28nm, 30nm, 32nm, 34nm, 36nm, 38nm, or 40nm). Controlling the average pore size of the functional layer within the above range is beneficial for embedding the copper foil layer into the surface of the functional coating, improving the adhesion between the functional coating and the copper foil layer, further enhancing the structural stability of the negative electrode current collector, and improving the welding yield of the negative electrode current collector.
[0043] According to some specific implementations, the average pore size of the functional layer is smaller than the average pore size of the main layer. The average pore size of the main layer is 30nm-50nm, and the average pore size of the functional layer is 25nm-40nm.
[0044] According to some specific implementations, the ratio of the average pore size of the main layer to the average pore size of the functional layer is 1.1-1.3, the average pore size of the main layer is 30nm-50nm, and the average pore size of the functional layer is 25nm-40nm.
[0045] In some embodiments, the substrate layer comprises at least one of unmodified polyethylene, modified polyethylene, unmodified polypropylene, modified polypropylene, unmodified polyethylene terephthalate, and modified polyethylene terephthalate.
[0046] In some embodiments, the main body layer comprises at least one of unmodified polyethylene, unmodified polypropylene, and unmodified polyethylene terephthalate.
[0047] In some embodiments, the negative electrode current collector satisfies the following relationship: 0.05 ≤ d / D ≤ 0.5 (e.g., 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5), where d is the thickness of the functional layer in μm, and D is the thickness of the substrate layer in μm. Controlling the negative electrode current collector to satisfy the above relationship ensures improved high-temperature resistance while maintaining a suitable average pore size in the functional layer, further enhancing the adhesion between negative electrode current collector layers, and thus further improving the structural stability of the negative electrode current collector.
[0048] In some embodiments, the thickness D of the substrate layer is 2μm-10μm (e.g., 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm).
[0049] According to some specific implementation methods, D is 2-10, and the negative electrode current collector satisfies the following relationship: 0.05≤d / D≤0.5.
[0050] In some embodiments, such as Figure 1 As shown, the copper foil layer 12 includes a first copper foil layer 121 and a second copper foil layer 122. The first copper foil layer 121 is located on the surface of the substrate layer 11, and the second copper foil layer 122 is located on the surface of the first copper foil layer 121 away from the substrate layer 11. It can be understood that the first copper foil layer 121 is also located on the surface of the functional layer 111.
[0051] In some embodiments, the thickness of the first copper foil layer is less than the thickness of the second copper foil layer.
[0052] In some embodiments, the thickness of the first copper foil layer is 50nm-200nm (e.g., 50nm, 80nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm).
[0053] According to some specific implementations, the thickness of the first copper foil layer is less than the thickness of the second copper foil layer, and the thickness of the first copper foil layer is 50nm-200nm.
[0054] A second aspect of the present invention provides a method for preparing the negative electrode current collector described in the first aspect of the present invention, the method comprising the following steps: S1: Pretreatment: The base film is subjected to atmospheric pressure plasma treatment to obtain a hydrophilic base film; S2: Modification preparation of a substrate layer with a functional layer on the surface: A photoinitiator, a crosslinking monomer, and a first solvent are brought into a first contact to form a first solution. The first solution is coated onto the surface of the hydrophilic base film through a first coating process to form a substrate layer including a wet film. The substrate layer including the wet film is placed in an oven for a first treatment, and then the temperature of the oven is adjusted for a second treatment to obtain a substrate layer including a dry film. The substrate layer including the dry film is placed under an ultraviolet light source for irradiation, so that the surface of the substrate layer undergoes a crosslinking reaction to obtain a substrate layer including a functional layer. S3: Prepare a metal layer on the surface of the functional layer: deposit a first copper foil layer on the opposite two sides of the substrate layer including the functional layer, and form a second copper foil layer by electroplating on the surface of the first copper foil layer.
[0055] In some embodiments, the thickness of the base film is 2μm-10μm (e.g., 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm).
[0056] In some embodiments, the porosity of the base film is less than or equal to 10% (e.g., 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%).
[0057] In some embodiments, the atmospheric pressure plasma treatment process is corona treatment, wherein the corona conditions include: a power of 1.5KW-3KW (e.g., 1.5KW, 1.8KW, 2KW, 2.2KW, 2.4KW, 2.6KW, 2.8KW, 3KW) and a time of 0.1s-10s (e.g., 0.1s, 0.5s, 1s, 2s, 3s, 4s, 5s, 6s, 7s, 8s, 9s, 10s). After plasma treatment, the surface of the base film is modified from hydrophobic to hydrophilic, which is beneficial for coating the base film surface to form a wet film.
[0058] In some embodiments, the first solvent includes one or more of acetone, butanone, ethyl acetate, toluene, and xylene.
[0059] In some embodiments, the photoinitiator has a mass fraction of 0.1%-5% (e.g., 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%) based on the total weight of the first solution, and the crosslinking monomer has a mass fraction of 0.05%-2.5% (e.g., 0.05%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%).
[0060] In some embodiments, the first solution is a transparent, phase-free crosslinking coating solution.
[0061] In some embodiments, the thickness of the wet film on one side of the substrate layer comprising the wet film is 5 μm-30 μm (e.g., 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm). By controlling the thickness of the wet film on one side, the thickness of the functional layer and the weight ratio of the crosslinked structural units in the functional layer can be controlled. The purpose of forming a wet film on the surface of the substrate layer is to allow the crosslinking monomers and photoinitiators to be uniformly distributed in the film layer and on the surface of the wet film. It is understood that the thickness of the wet film is not equal to the thickness of the functional layer. In subsequent processing, the solvent in the wet film will evaporate, and the photoinitiator and crosslinking monomers will penetrate into the surface of the substrate layer for modification, forming the functional layer. That is, after subsequent processing, the wet film will be consumed. Therefore, the functional layer is part of the substrate layer and is a coating formed by the modification of the surface of the substrate layer by the photoinitiator and crosslinking monomers, rather than a new coating layer added to the surface of the substrate layer by coating the wet film.
[0062] In some embodiments, the first coating process is selected from at least one of blade coating, dip-coating, or microgravure coating.
[0063] In some embodiments, the first treatment is a low-temperature drying treatment, and the conditions of the first treatment include: a temperature of 30°C-50°C (e.g., 30°C, 33°C, 35°C, 38°C, 40°C, 42°C, 45°C, 48°C, 50°C), and a time of 1 min-5 min (e.g., 1 min, 2 min, 3 min, 4 min, 5 min). Under the first treatment, most of the first solvent in the wet film will slowly evaporate. Controlling the conditions of the first treatment within the above range can ensure that the first solvent evaporates slowly, avoiding excessively high temperatures and excessively rapid evaporation of the first solvent, which can lead to problems such as peeling, orange peel, cracking, and uneven thickness of the wet film surface. This, in turn, affects the subsequent crosslinking reaction, resulting in uneven crosslinking, damaging the interfacial integrity between the substrate layer and the copper foil layer, and is not conducive to further improving the high-temperature resistance of the substrate layer and the bonding force between the substrate layer and the copper foil layer.
[0064] In some embodiments, the second treatment is a heat drying treatment, and the conditions of the second treatment include: a temperature of 80°C-120°C (e.g., 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C), and a time of 5 min-15 min (e.g., 5 min, 7 min, 9 min, 11 min, 13 min, 15 min). Controlling the conditions of the second treatment within the above range enables sufficient removal of the residual first solvent in the wet film, turning the surface of the wet film into a dry state, thereby ensuring that the photoinitiator and crosslinking monomer in the wet film penetrate into the surface layer of the substrate layer as much as possible.
[0065] In this invention, both the first and second treatments enable the photoinitiator and crosslinking agent to penetrate into the surface of the substrate layer. The first treatment involves low-temperature drying, followed by heat drying (the second treatment). This ensures that the photoinitiator and crosslinking monomers slowly and uniformly penetrate the surface of the substrate layer, thereby reducing or even eliminating the risk of uneven crosslinking and further improving the high-temperature resistance of the negative electrode current collector. It is understood that after the first and second treatments, a small amount of photoinitiator and / or crosslinking monomers may still remain on the surface of the substrate layer. To ensure the adhesion between the copper foil layer and the substrate layer, and to maintain the high-temperature resistance of the negative electrode current collector, the residual amount of crosslinking monomers and / or photoinitiator on the surface of the substrate layer is less than or equal to 2000 ppm.
[0066] In some embodiments, the irradiance of the ultraviolet light source is 3000 mJ / cm². 2 -20000 mJ / cm 2 (3000mJ / cm) 2 5000mJ / cm 2 7000mJ / cm 2 9000mJ / cm 2 11000mJ / cm 2 13000mJ / cm 2 15000mJ / cm 2 18000mJ / cm 2 20000mJ / cm 2 By controlling the irradiation of the ultraviolet light source within the above-mentioned range, the cross-linking reaction can be promoted, while reducing or even avoiding the risk of excessive cross-linking.
[0067] Under ultraviolet (UV) light irradiation, a cross-linking reaction is triggered. First, the photoinitiator absorbs UV light of a specific wavelength (e.g., 250nm-350nm). The photoinitiator, absorbing UV light, transitions from its ground state to a high-energy excited state. The molecule in the high-energy excited state can abstract hydrogen atoms from the chain structure, transforming the inert molecular chain structure into a highly reactive macromolecular free radical. After the photoinitiator free radical abstracts hydrogen, the originally inert long-chain molecular structure becomes a macromolecular free radical with unpaired electrons, exhibiting extremely high reactivity. Theoretically, two macromolecular free radicals can directly collide and couple to form carbon-carbon cross-linking bonds. However, in solid films, the long-chain structure is difficult to move, and direct coupling efficiency is very low. Therefore, the cross-linking reaction requires the participation of cross-linking monomers. The small molecules of the cross-linking monomers can rapidly connect different chain structures through double bond addition reactions between macromolecular free radicals, forming a stable three-dimensional network structure, thereby improving the high-temperature resistance of the negative electrode current collector and increasing the welding yield. It is understandable that the crosslinking reaction takes place on the surface of the substrate layer, rather than in the wet film. Therefore, the functional layer belongs to the substrate layer and is located on the surface of the substrate layer.
[0068] In some embodiments, the photoinitiator abstracts hydrogen from the chain-like structural backbone under ultraviolet light excitation to form a highly active macromolecular free radical. This macromolecular free radical can not only react with crosslinking monomers to build a three-dimensional crosslinking network, but also undergo a coupling termination reaction with the reducing free radical of the initiator, thereby grafting the structural unit from the photoinitiator onto the carbon atoms in the backbone of the chain-like structural unit in the form of covalent bonds.
[0069] In some embodiments, the process for forming the first copper foil layer is selected from chemical copper plating and magnetron sputtering copper plating.
[0070] In some embodiments, the electroplating solution includes copper sulfate pentahydrate (CuSO4·5H2O), sulfuric acid (H2SO4), and a solution containing chloride ions (Cl). - Inorganic additives, tetrahydrothiazolyl thiophene, sodium poly(dihexanediol) sulfonate, and polyethylene glycol (PEG-600).
[0071] In some embodiments, the concentration of copper sulfate pentahydrate in the electroplating solution is 100 g / L to 300 g / L (e.g., 100 g / L, 120 g / L, 140 g / L, 160 g / L, 180 g / L, 200 g / L, 220 g / L, 240 g / L, 260 g / L, 280 g / L, 300 g / L).
[0072] In some embodiments, the concentration of sulfuric acid in the electroplating solution is 20 g / L to 90 g / L (e.g., 20 g / L, 30 g / L, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L).
[0073] In some embodiments, the concentration of the inorganic additive containing chloride ions in the electroplating solution is 10 mg / L to 100 mg / L (e.g., 10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, 90 mg / L, 100 mg / L).
[0074] In some embodiments, the concentration of tetrahydrothiazothione in the electroplating solution is 0.0005 g / L to 0.001 g / L (e.g., 0.0005 g / L, 0.0006 g / L, 0.0007 g / L, 0.0008 g / L, 0.0009 g / L, 0.001 g / L).
[0075] In some embodiments, the concentration of sodium polyhexadecanesulfonate in the electroplating solution is 0.01 g / L to 0.02 g / L (e.g., 0.01 g / L, 0.012 g / L, 0.014 g / L, 0.016 g / L, 0.018 g / L, 0.02 g / L).
[0076] In some embodiments, the concentration of polyethylene glycol in the electroplating solution is 0.03 g / L to 0.05 g / L (e.g., 0.03 g / L, 0.032 g / L, 0.034 g / L, 0.036 g / L, 0.038 g / L, 0.04 g / L, 0.042 g / L, 0.044 g / L, 0.046 g / L, 0.048 g / L, 0.05 g / L).
[0077] In some embodiments, the average molecular weight of polyethylene glycol is about 6000 g / mol.
[0078] In some embodiments, the electroplating conditions include: a time of 0.5 min to 5 min (e.g., 0.5 min, 0.8 min, 1 min, 1.2 min, 1.4 min, 1.6 min, 1.8 min, 2 min, 2.5 min, 3 min, 3.5 min, 4 min, 4.5 min, 5 min), and a current density of 2 mA / cm². 2 -30mA / cm 2 (For example, 2mA / cm) 2 4mA / cm 2 6mA / cm 2 8mA / cm 2 10mA / cm 2 12mA / cm 2 14mA / cm 2 16mA / cm 2 18mA / cm2 20mA / cm 2 22mA / cm 2 24mA / cm 2 26mA / cm 2 28mA / cm 2 30mA / cm 2 The temperature range is 30℃-50℃ (e.g., 30℃, 33℃, 35℃, 38℃, 40℃, 42℃, 45℃, 48℃, 50℃).
[0079] In this invention, the reason for preferentially forming the first copper foil layer on the surface of the functional layer is that the functional layer is not conductive. The copper foil layer is formed by electroplating, which requires the substrate to be conductive. In order to facilitate the electroplating to form the second copper foil layer, the first copper foil layer with conductivity is preferentially formed on the surface of the functional layer.
[0080] In some embodiments, before pretreating the base film, the surface of the base film is cleaned with a second solvent. Cleaning can remove impurities adsorbed on the surface of the base film and improve the uniformity of subsequent wet film coating.
[0081] In some embodiments, the second solvent is selected from at least one of ethanol, isopropanol, and water.
[0082] A third aspect of the present invention provides a battery comprising a negative electrode sheet, the negative electrode sheet comprising the negative electrode current collector described in the first aspect of the present invention and / or the negative electrode current collector prepared by the method described in the second aspect of the present invention.
[0083] In some embodiments, the battery is a lithium-ion secondary battery.
[0084] The battery of the present invention has high mass energy density and high safety performance because it includes the negative electrode current collector described in the first aspect of the present invention and / or the negative electrode current collector prepared by the method described in the second aspect of the present invention.
[0085] The present invention will be described in detail below through embodiments. The embodiments described herein are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0086] The following examples illustrate the negative electrode current collector of the present invention.
[0087] Example 1 Preparation of negative electrode current collector: The surface of the base film (polyethylene PE, 4 μm thick, 5% porosity) was cleaned using a second solvent (anhydrous ethanol).
[0088] S1: Pretreatment: The base film is subjected to atmospheric pressure plasma treatment to obtain a hydrophilic base film; S2: Modification preparation of a substrate layer with a functional layer on the surface: A first solution is formed by first contacting a photoinitiator (benzophenone), a crosslinking monomer (tripropylene isocyanurate), and a first solvent (acetone). The first solution is coated onto the surface of the hydrophilic base film through a first coating process to form a substrate layer including a wet film. The substrate layer including the wet film is placed in an oven for a first treatment, and then the temperature of the oven is adjusted for a second treatment to obtain a substrate layer including a dry film. The substrate layer including the dry film is placed under an ultraviolet light source for irradiation, so that the surface of the substrate layer undergoes a crosslinking reaction to obtain a substrate layer including a functional layer. S3: Prepare a metal layer on the surface of the functional layer: deposit a first copper foil layer on the opposite two sides of the substrate layer including the functional layer, and form a second copper foil layer by electroplating on the surface of the first copper foil layer.
[0089] The atmospheric pressure plasma treatment process is corona treatment, with the following conditions: power 2kW, time 0.2s. Based on the total weight of the first solution, the photoinitiator accounts for 1% of the weight, and the crosslinking monomer accounts for 2% of the weight. The thickness of the single-sided wet film is 10±2μm; the first coating process is microgravure coating. The conditions for the first treatment are: temperature 40℃, time 2min. The conditions for the second treatment are: temperature 90℃, time 10min. The irradiance from the ultraviolet light source is 3000mJ / cm². 2 The first copper foil layer was formed by magnetron sputtering copper plating, with a thickness of 100 nm. The plating solution consisted of copper sulfate pentahydrate (CuSO4·5H2O), sulfuric acid (H2SO4), and inorganic additive Cl. - The electroplating solution contains tetrahydrothiazolium-1, sodium poly(dihexanediol) sulfonate, and polyethylene glycol (PEG-600). The concentrations of copper sulfate pentahydrate, sulfuric acid, inorganic additives (including chloride ions), tetrahydrothiazolium-1, sodium poly(dihexanediol) sulfonate, and polyethylene glycol in the solution are as follows: 200 g / L; 50 g / L; 50 mg / L; 1 mg / L; 15 mg / L; 40 mg / L; 3 min; and 15 mA / cm². 2 The electroplating temperature is 35℃; the thickness of the second copper foil layer is 900nm.
[0090] In the prepared negative electrode current collector, the main layer is composed of polyethylene, the functional layer is composed of polyethylene and modified polyethylene, and the repeating unit of the chain structure is... -CH2-CH2- The cross-linked structural unit is Based on the total weight of the substrate layer, the weight ratio of the crosslinked structure is 45.2%, and the polar groups are carbonyl (C=O) and isocyanurate rings (containing C=O and C-N polar bonds); satisfying the following: in the thickness direction of the substrate layer, from the surface of the functional layer to the direction close to the main layer, the weight ratio of the crosslinked structural units in the functional layer decreases; the average pore size of the main layer is 43.3 nm, the average pore size of the functional layer is 35 nm, the thickness D of the substrate layer is 4 μm, d / D=0.45, and there are no residual crosslinked monomers or residual photoinitiators on the surface of the substrate layer (when the residual amount of residual substances (photoinitiators and / or crosslinked monomers) on the surface of the substrate layer is less than or equal to 100 ppm, it is considered that there are no residual crosslinked monomers or residual photoinitiators on the surface of the substrate layer).
[0091] Example 2 group This set of examples illustrates the effects of changes in the composition of the base film.
[0092] Example 2a The preparation process of the negative electrode current collector was carried out according to Example 1, except that the base membrane was composed of polypropylene with a porosity of 5%. In the prepared negative electrode current collector, the main layer was composed of polypropylene, the functional layer was composed of modified polypropylene, and the repeating unit of the chain structure was... -CH(CH3)-CH2- Based on the total weight of the substrate layer, the weight ratio of the crosslinked structural units is 20.4%; satisfying the following: in the thickness direction of the substrate layer, from the surface of the functional layer to the direction close to the main layer, the weight ratio of the crosslinked structural units in the functional layer shows a decreasing trend; the average pore size of the main layer is 49.4 nm, the average pore size of the functional layer is 39.8 nm, and there are no residual crosslinked monomers or residual photoinitiators on the surface of the substrate layer.
[0093] Example 2b The preparation process of the negative electrode current collector was carried out according to Example 1, except that the base membrane was composed of polyethylene terephthalate (PET) with a porosity of 5%. In the prepared negative electrode current collector, the main layer was composed of PET, the functional layer was composed of modified PET, and the repeating unit of the chain structure was... -O-CH2-CH2-O-CO-C6H4-CO- Based on the total weight of the substrate layer, the weight ratio of crosslinked structural units is 10.2%, and the polar groups are carbonyl (C=O) and isocyanurate cyclic groups (containing C=O and C-N polar bonds) as well as the ester groups (-COO-) inherent in the base film itself; satisfying the following: in the thickness direction of the substrate layer, from the surface of the functional layer to the direction close to the main layer, the weight ratio of crosslinked structural units in the functional layer shows a decreasing trend; the average pore size of the main layer is 45.1 nm, the average pore size of the functional layer is 41.2 nm, and there are no residual crosslinked monomers or residual photoinitiators on the surface of the substrate layer.
[0094] Example 3 Group This set of examples illustrates the effects of changing the weight percentage of cross-linked structures in the substrate layer by adjusting the irradiation dose of the ultraviolet light source.
[0095] This embodiment group is based on Embodiment 1, except that the weight ratio of the cross-linked structure in the substrate layer is changed, as shown in Table 1-1.
[0096] Example 4 group This set of examples illustrates the effects of changing the average pore size of the functional layer by adjusting the mass fraction of the photoinitiator in the first solution.
[0097] This embodiment group is based on Embodiment 1, except that the average pore size of the functional coating is changed, as detailed in Table 1-1.
[0098] Table 1-1 Example 5 group This set of examples illustrates the effects of changing the d / D ratio by adjusting the thickness of the wet film.
[0099] This embodiment group is carried out with reference to Embodiment 1, except that d / D is changed, as detailed in Tables 1-2.
[0100] Table 1-2 Example 6 group This set of examples illustrates the effects of changing the specific choice of crosslinking monomers.
[0101] This set of examples is based on Example 1, except that the specific selection of crosslinking monomers is changed, as detailed in Tables 1-3.
[0102] Table 1-3 Example 7 group This set of examples illustrates the effects of changing the specific choice of photoinitiator.
[0103] Example 7a The procedure was carried out in accordance with Example 1, except that the photoinitiator was changed to ITX and the residual amount of residual material on the surface of the substrate layer was less than or equal to 100 ppm.
[0104] Example 7b The procedure was carried out in accordance with Example 1, except that the photoinitiator was changed to BDK and the residual amount of residual material on the substrate layer surface was less than or equal to 100 ppm.
[0105] Example 7c The procedure was carried out in accordance with Example 1, except that the photoinitiator was changed to 1-hydroxycyclohexylphenyl ketone, and the residual amount of residual material on the surface of the substrate layer was less than or equal to 100 ppm.
[0106] Example 7d The procedure was carried out in accordance with Example 1, except that the photoinitiator was changed to TPO and the residual amount of residual material on the surface of the substrate layer was less than or equal to 100 ppm.
[0107] Comparative Example 1 The procedure was carried out in accordance with Example 1, except that a copper foil layer was directly deposited on the surface of the base film without modifying the surface layer of the base film.
[0108] Comparative Example 2 The procedure is performed according to Example 1, except that step S2 is replaced with: 5g of hexamethylene diisocyanate and 5g of polyester resin with a weight average molecular weight of 20,000 were dissolved in a mixed solvent of 10g of styrene and 80g of methylcyclohexane. Then, 0.1g of dibutyltin dilaurate was added, and the mixture was stirred at 80℃ for 2 hours while being ultrasonically treated to obtain a modified slurry. The solid content of the modified slurry was 10wt%. The weight ratio of styrene to methylcyclohexane in the mixed solvent was 1:8. The modified slurry was coated on both sides of the base film using a microgravure coating machine (Kejing, MSK-AFA-MG200), and cured at 80℃ for 10 minutes to obtain a modified layer. In step S3, the first copper foil layer is formed on the surface of the modified layer, and the second copper foil layer is formed on the surface of the first copper foil layer. The residual amount of residual material on the surface of the substrate layer is less than or equal to 100 ppm.
[0109] Comparative Examples 3-4 The same procedure was followed as in Example 1, except that the weight percentage of the cross-linked structure in the substrate layer was changed by adjusting the thickness of the wet film.
[0110] Table 1-4 Test case The negative electrode current collectors prepared by the examples and comparative examples were subjected to the following tests.
[0111] 1. Heat shrinkage test Three square samples with a size of 10cm×10cm were cut from the prepared negative electrode current collector. The MD and TD directions were marked to ensure that there were no wrinkles. The samples were placed in a constant temperature drying oven at 135℃ for 15min. After taking them out, the lengths in the MD and TD directions were recorded, and the longitudinal thermal shrinkage rate was calculated.
[0112] 2. Peel strength test Cut a 2.5cm wide strip from the prepared negative electrode current collector, attach it to the copper foil layer with tape for clamping, and use a tensile testing machine to peel the copper foil layer from the substrate layer at a 180° angle and a speed of 100mm / min. Take the average force of the stable segment of the peel curve, divide it by the width of 2.5cm, and obtain the peel strength (unit: N / cm). The standard requirement is ≥0.8 N / cm.
[0113] 3. Welding yield test Twenty 2cm×5cm samples were cut from the prepared negative electrode current collector and ultrasonically welded to nickel electrode tabs using an ultrasonic welding machine. The welding effect was observed and the cases of incomplete or missing welds were recorded.
[0114] The test results are recorded in Table 2.
[0115] Table 2 As can be seen from Table 2, the comparison between the comparative examples and the embodiments shows that the negative electrode current collector prepared by the embodiments has a lower thermal shrinkage rate, a higher peel strength, and a higher welding yield. This indicates that by setting a functional layer on the surface of the substrate layer and controlling the composition of the functional layer and the weight ratio of the cross-linked structural units in the substrate layer, the high temperature resistance, structural stability, and welding yield of the negative electrode current collector are improved.
[0116] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A negative electrode current collector, characterized in that, The negative electrode current collector includes a substrate layer and a copper foil layer. The substrate layer is composed of a functional layer and a main layer. In the thickness direction of the substrate layer, the functional layer is located on both sides of the main layer, and the copper foil layer is located on the side of the functional layer away from the main layer. The functional layer comprises several cross-linked structures, each including chain structural units and cross-linked structural units. Each cross-linked structural unit connects at least two chain structural units in the form of covalent bonds. Based on the total weight of the substrate layer, the weight percentage of the cross-linked structures is 5%-50%.
2. The negative electrode current collector according to claim 1, wherein, The repeating units of the chain-like structural unit are selected from... -[C(R1R2)-C(R3R4)]- , -[O-CH2-CH2-O-CO-C6H4-CO]- One or more of the following, wherein R1, R2, R3, and R4 are each independently selected from hydrogen atom, methyl, ethyl, and propyl. Indicates the connection site; And / or, the crosslinked structural unit includes at least two connection sites, which are connected to carbon atoms in the backbone of the chain-like structural unit. Preferably, the crosslinked structural unit is selected from... , , -CH2-CH-COO-CH2-CH(CH3)-O-CH2-CH(CH3)-O-CH2-CH(CH3)-O-CO-CH-CH2- , -CH2-CH-COO-(CH2)6-O-CO-CH-CH2- , At least one of them, Indicates the connection site; And / or, the crosslinked structural unit includes the polar group; And / or, the functional layer further comprises a plurality of chain structures, wherein the chain structures do not include the crosslinking structural units, and the repeating units of the chain structures are selected from... -[C(R1R2)-C(R3R4)]- , -[O-CH2-CH2-O-CO-C6H4-CO]- One or more of the following, wherein R1, R2, R3, and R4 are each independently selected from hydrogen atom, methyl, ethyl, and propyl. Indicates the connection site; And / or, in the thickness direction of the substrate layer, from the surface of the functional layer to the direction closer to the main layer, the weight percentage of the cross-linked structure in the functional layer shows a decreasing trend.
3. The negative electrode current collector according to claim 1, wherein, The average pore size of the functional layer is smaller than the average pore size of the main layer; And / or, the average pore size of the main layer is 30nm-50nm, and / or, the average pore size of the functional layer is 25nm-40nm; And / or, the substrate layer comprises at least one of unmodified polyethylene, modified polyethylene, unmodified polypropylene, modified polypropylene, unmodified polyethylene terephthalate, and modified polyethylene terephthalate; And / or, the main body layer comprises at least one of unmodified polyethylene, unmodified polypropylene, and unmodified polyethylene terephthalate; And / or, the components of the functional layer include at least one of unmodified polyethylene, modified polyethylene, unmodified polypropylene, modified polypropylene, unmodified polyethylene terephthalate, and modified polyethylene terephthalate.
4. The negative electrode current collector according to claim 1, wherein, The negative electrode current collector satisfies the following relationship: 0.05≤d / D≤0.5, where d is the thickness of the functional layer in μm and D is the thickness of the substrate layer in μm; And / or, the thickness D of the substrate layer is 2μm-10μm; And / or, the components of the functional layer further include polar groups selected from at least one of ester groups, isocyanurate cyclo groups, hydroxyl groups, ether groups, and carbonyl groups.
5. The negative electrode current collector according to any one of claims 1-4, wherein, The cross-linking structural unit is derived from a cross-linking monomer, which includes one or more of trimethylolpropane triacrylate, triallyl isocyanurate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, and pentaerythritol triacrylate. And / or, the components of the functional layer further include structural units from a photoinitiator, wherein the structural units from the photoinitiator are grafted to atoms in the backbone of the chain structural unit, and the photoinitiator includes one or more of 2-isopropylthioxanthone, benzophenone, benzoyldimethyl ketal, 1-hydroxycyclohexylphenyl ketone, and 2,4,6-trimethylbenzoyldiphenylphosphine oxide; And / or, the copper foil layer includes a first copper foil layer and a second copper foil layer, wherein the first copper foil layer is located on the surface of the substrate layer and the second copper foil layer is located on the surface of the first copper foil layer.
6. The negative electrode current collector according to claim 5, wherein, The residual amount of surface crosslinking monomers and / or photoinitiators in the substrate layer is less than or equal to 2000 ppm; And / or, the thickness of the first copper foil layer is less than the thickness of the second copper foil layer; And / or, the thickness of the first copper foil layer is 50nm-200nm.
7. A method for preparing the negative electrode current collector according to any one of claims 1-6, characterized in that, The method Includes the following steps: S1: Pretreatment: The base film is subjected to atmospheric pressure plasma treatment to obtain a hydrophilic base film; S2: Modification preparation of a substrate layer with a functional layer on the surface: A photoinitiator, a crosslinking monomer, and a first solvent are brought into a first contact to form a first solution. The first solution is coated onto the surface of the hydrophilic base film through a first coating process to form a substrate layer including a wet film. The substrate layer including the wet film is placed in an oven for a first treatment, and then the temperature of the oven is adjusted for a second treatment to obtain a substrate layer including a dry film. The substrate layer including the dry film is placed under an ultraviolet light source for irradiation, so that the surface of the substrate layer undergoes a crosslinking reaction to obtain a substrate layer including a functional layer. S3: Prepare a metal layer on the surface of the functional layer: deposit a first copper foil layer on the opposite two sides of the substrate layer including the functional layer, and form a second copper foil layer by electroplating on the surface of the first copper foil layer.
8. The method according to claim 7, wherein, The thickness of the base film is 2μm-10μm; And / or, the porosity of the base film is less than or equal to 10%; And / or, the first solvent includes one or more of acetone, butanone, ethyl acetate, toluene, and xylene; And / or, based on the total weight of the first solution, the mass fraction of the photoinitiator is 0.1%-5%, and the mass fraction of the crosslinking monomer is 0.05%-2.5%; And / or, in the substrate layer including the wet film, the thickness of the wet film on one side is 5μm-30μm.
9. The method according to claim 7, wherein, The atmospheric pressure plasma treatment process is corona treatment, and the conditions for corona treatment include: power of 1.5kW-3kW and time of 0.1s-10s. And / or, the first coating process is selected from at least one of blade coating, dip-coating, or microgravure coating; And / or, the conditions for the first treatment include: a temperature of 30°C-50°C and a time of 1 min-5 min; And / or, the conditions for the second treatment include: a temperature of 80°C-120°C and a time of 5 min-15 min; And / or, the irradiance of the ultraviolet light source is 3000 mJ / cm². 2 -20000 mJ / cm 2 ; And / or, the process for forming the first copper foil layer is selected from one of chemical copper plating and magnetron sputtering copper plating; And / or, prior to pretreatment of the base film, the surface of the base film is cleaned using a second solvent selected from at least one of ethanol, isopropanol, and water.
10. A battery, characterized in that, The battery includes a negative electrode sheet, which includes the negative electrode current collector according to any one of claims 1-6 and / or the negative electrode current collector prepared by the method according to any one of claims 7-9.